OPTIMASI GEL EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi Linn) SEBAGAI ANTIBAKTERI Staphylococcus aureus - Dwi Saryanti; Iwan Setiawan; Pingki Retnosari (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Belimbing wuluh leaves (DBW) are a plant that has antibacterial properties with active flavonoid compounds. The leaf extract with a concentration of 10% has a strong inhibitory ability against Staphylococcus aureus (SA) bacteria. Gel preparations have several advantages, including having water content with cooling, soothing, moisturizing properties, easy to use, easy to penetrate the skin, and provide a healing effect. The aim of this research was to determine the optimal comparison of CMC-Na and Carbopol 940 bases in starfruit leaf extract gel preparations using the Simplex lattice design (SLD) method and to evaluate the antibacterial activity on SA bacteria. DBW extraction uses a maceration extraction method using 96% ethanol. The optimal DBW extract gel formula was determined using the Simplex Lattice Design (SLD) method using Design Expert 11. Verification of the optimal DBW extract gel formula using one sample T-test. The antibacterial test on SA used the well method and the results were analyzed using One Way Anova. The optimal formula obtained was tested for stability using freeze thaw cycling and acceptability tested. The optimal concentration of CMC-Na and Carbopol 940 produced by the SLD method is CMC-Na of 35% (0.7 g) and Carbopol 940 of 65% (1.3 g) with a total base weight of 2g. The results of the antibacterial test showed that the gel preparation could inhibit SA bacteria with an inhibition zone of 14.43 ± 0.707 mm. The results of the optimal formula verification test obtained a p value of >0.05, so the data obtained was not significantly different and it can be said that the formula for the SLD method results was valid including pH, viscosity, spreadability, adhesion power. The optimal gel formula obtained shows that the preparation is stable in storage and can be accepted by respondents.